FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI PENGGUNAAN JAMBAN KELUARGA DI DESA MARJANDI TONGAH KECAMATAN GUNUNG MERIAH KABUPATEN DELI SERDANG TAHUN 2013 - Saut Hasudungan Simatupang; surya dharma; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
One of the efforts made in the public health is privy maintain and improve the health of the community in the form of disease prevention , and restoration of health by government and society. Marjandi Tongah village is the village that has the lowest presence of latrines in the district of Gunung Meriah Deli serdang , and always use the river , ditch the sewage / faeces . Latrines is home throw human faeces so that bacteria in the dirty does not meet the environment, then the environment will look clean, so it has a beautiful aesthetic values, as well as not causing germs. This study aims to determine the factors associated with a participation of family latrines in the village Marjandi Tongah. The method is cross sectiona design. The population in this study families have not family latrines. The sample of the study was the total population of as many as 55 families, Analysis of the data using univariate and bivariate analysis using chi – square at 9 5% confidence level. The results showed variable knowledge ( p = 0.003 ) no relationship with the participation of family latrines. Attitude variable ( p = 0.0001 ) there is relationship with participation of family latrines. Variable availability of clean water ( p = 0.0001) there is a relationship with a participation of family latrines As well as the role of health workers variable ( p = 0.019 ) no relationship with the participation of family latrines. Health care workers are advised to Puskesmas Gunung Meriah and village chief counsel to increase its role in the community in the use and utilazation of latrines in the village Marjandi Tongah District of Gunung Meriah. Keyword : Health Efforts, Toilet,Participation of family latrines